The Munich Agreement of 1938 and contemporary threats to European Security - L. N. Anisimov (Московский журнал международного права, 2009)
The article discusses the aggressive essence of the Munich agreement of 1938 between the Nazi Germany, France, the fascist Italy and Great Britain, which allowed Hitler to divide (separate) Czech Republic and Slovakia and permitted secession of the Sudetskuju province. The recently declassified information by the Foreign Intelligence service of the Russian Federation tests about Poland’s connection to the Munich agreement. The author argues the invalid nature of the agreement. In the article also dwells on the contemporary European diplomacy that did not made adequate conclusions from the Munich agreement and supported aggressive actions of the USA against Yugoslavia (1999). Equally, placing American elements of the defense against missiles to the territory of Czech Republic and Poland create potential threats to European security.